Development of the BINP AMS complex at CCU SB RAS - Rastigeev, S.A.; Frolov, A.R.; Goncharov, A.D.; Klyuev, V.F.; Konstantinov, E.S.; Kutnykova, L.A.; Parkhomchuk, V.V.; Petrozhitskii, A.V. (Вопросы атомной науки и техники, 2012)
The accelerator mass spectrometer created at BINP is installed at CCU “Geochronology of the cenazoic era” for sample dating by the ¹⁴С isotope. Present status of AMS complex and the results of experiments for radiocarbon concentration measurements in test samples are presented. Созданный в ИЯФ ускорительный масс-спектрометр установлен в ЦКП «Геохронология кайнозоя» для датирования образцов по изотопу ¹⁴С. Представлены текущее состояние комплекса УМС и результаты экспериментов по измерению концентрации радиоуглерода в тестовых образцах. Створений у ІЯФ прискорювальний мас-спектрометр встановлено в ЦКП «Геохронологія кайнозою» для датування зразків по ізотопу ¹⁴С. Представлено поточний стан комплексу УМЗ і результати експериментів з вимірювання концентрації радіовуглецю в тестових зразках.